2008
DOI: 10.1007/s11746-008-1277-z
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of Canola Oil with Hydrogen Peroxide Catalyzed by Acidic Ion Exchange Resin

Abstract: Canola oil with an iodine value of 112/100 g, and containing 60% oleic acid and 20% linoleic acid, was epoxidised using a peroxyacid generated in situ from hydrogen peroxide and a carboxylic acid (acetic or formic acid) in the presence of an acidic ion exchange resin (AIER), Amberlite IR 120H. Acetic acid was found to be a better oxygen carrier than formic acid, as it produced about 10% more conversion of ethylenic unsaturation to oxirane than that produced by formic acid under otherwise identical conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 28 publications
5
117
1
1
Order By: Relevance
“…The mechanism for this reaction can be seen in Scheme 3. Despite having a higher rate of epoxide formation when formic acid is employed (Dinda et al, 2008), acetic acid is found to be a better choice as 10% higher conversion of ethylenic unsaturation to epoxides is observed compared to formic acid (Mungroo et al, 2008).…”
Section: Prilezhaev Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism for this reaction can be seen in Scheme 3. Despite having a higher rate of epoxide formation when formic acid is employed (Dinda et al, 2008), acetic acid is found to be a better choice as 10% higher conversion of ethylenic unsaturation to epoxides is observed compared to formic acid (Mungroo et al, 2008).…”
Section: Prilezhaev Reactionsmentioning
confidence: 99%
“…Two common oxidants employed in the industry are performic acid and peracetic acid, generated in-situ using hydrogen peroxide as the oxygen donor and a carboxylic acid such as formic acid (Ni and Salimon, 2012) or acetic acid. While the use of formic acid can be carried out with no catalyst requirement (Ni and Salimon, 2012), acetic acid requires an acid catalyst, either a strong inorganic acid (Dinda et al, 2008), such as HCl, HNO 3 , H 3 PO 4 and the most widely used is H 2 SO 4 , or acidic ion exchange resins (AIER) (Cooney et al, 2011;Mungroo et al, 2008). The mechanism for this reaction can be seen in Scheme 3.…”
Section: Prilezhaev Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced rate of per acid formation was anticipated with an increase catalyst loading and hydrogen peroxide concentration followed by an increase in the OOC [49,52]. Figure S7a and b describes the effect of catalyst loading and hydrogen peroxide on the course of epoxide formation.…”
Section: Effect Of Catalyst Loading and Substrate Molar Ratio On Oocmentioning
confidence: 97%
“…However, in spite of such versatility, some of the disadvantages like low toughness, high brittleness and non-biodegradability restricting their utilizations in many advanced applications. Also, the global concern regarding the degradability of polymeric materials in environment compelled the scientists to explore the renewable resources in the production of useful materials (Velayutham et al, 2012;Yang et al, 2011;Biermann et al, 2000;Mungroo et al, 2008;Singh, et al, 2012). Therefore, to overcome such limitations, bio based epoxy resins were produced from vegetable oils.…”
Section: Introductionmentioning
confidence: 99%